Programmable load API development for hybrid micro grid - Goh, Yi Hui (2016)
In order to provide researchers working on the Hybrid Micro Grid (HMG) system with a more efficient way to control and monitor the programmable loads, an application was developed by integrating several of its building blocks know as Application Program Interface (API). The first phase focused on the development of the application module. A serial communication link between the load and the computer was developed through a Python library known as pySerial. The load can be operated in either manual or autonomous mode, with the latter requiring a database for the user to pre-set commands to be executed during stipulated time. Commands entered were cross-referenced with a list of executable commands to check for correctness before being transmitted to the load for execution. Executed commands were auto-saved in a text file for future references. The second phase looked into the development of a Graphical User Interface (GUI) through software called Qt Designer to provide users with an interactive and friendly environment to control the application. A program called PyQt4 was used to convert Qt file to Python file to allow customization of the user interface through Python programming. Some widgets in the interface were connected to APIs developed while others were used to display add-ons such as a real-time load curve and command history. The final phase involved the development of a WebSocket protocol using client-server architecture to enable transmitting and receiving of commands through a wireless network. This would enable devices running the application to communicate wirelessly with the programmable load. Upon completion, wireless controlling and monitoring of the programmable load under real-time condition was made possible.